Psychometric Tests and Spatial Navigation: Data From the Baltimore Longitudinal Study of Aging - Wei, Eric X.; Anson, Eric R.; Resnick, Susan M.; Agrawal, Yuri (Frontiers in Neurology, 2020)
Spatial cognition is the process by which individuals interact with their spatial environment. Spatial cognition encompasses the specific skills of spatial memory, spatial orientation, and spatial navigation. Prior studies have shown an association between psychometric tests of spatial ability and self-reported or virtual measures of spatial navigation. In this study, we examined whether psychometric spatial cognitive tests predict performance on a dynamic spatial navigation task that involves movement through an environment. We recruited 151 community-dwelling adult participants (mean (SD) age 69.7 (13.6), range 24.6-93.2) from the Baltimore Longitudinal Study of Aging (BLSA). Spatial navigation ability was assessed using the triangle completion task (TCT), and two quantities, the angle and distance of deviation, were computed. Visuospatial cognitive ability was assessed primarily using the Card Rotations Test. Additional tests of executive function, memory, and attention were also administered. In multiple linear regression analyses adjusting for age, sex, race, and education, cognitive tests of visuospatial ability, executive function, and perceptual motor speed and integration were significantly associated with spatial navigation, as determined by performance on the TCT. These findings suggest that dynamic spatial navigation ability is related to spatial memory, executive function, and motor processing speed.